Can Primary School Mathematics Performance Be Predicted by Longitudinal Changes in Physical Fitness and Activity Indicators? - Sember, Vedrana; Jurak, Gregor; Starc, Gregor; Morrison, Shawnda A. (Frontiers in Psychology, 2022)
Objective: To determine to what extent physical fitness indicators and/or moderate to vigorous physical activity (MVPA) may account for final mathematics academic performance (APmath) awarded at the end of primary school. Methods: School-aged youth were sampled in a repeated-measures, longitudinal design in Grade 6 (~11 y), and again in Grade 9 (~14 y). The youth (N=231, 111 girls) completed a fitness test battery consisting of: flamingo balance test, standing long jump, backward obstacle course, plate tapping, sit ups, sit and reach, handgrip, and 20-m shuttle run. APmath scores were obtained for all children at the end of Grade 5, end of Grade 8, and end of Grade 9 (their final year of primary school). In a sub-sample of Grade 6 youth (N=50, 29 girls), MVPA was measured objectively via SenseWear Pro Armbands (MVPAOB) for seven consecutive days, with measurements repeated in Grade 9. Results: Math scores decreased from Grade 6 to 9 for both boys and girls (95%CI: -0.89 to -0.53, p<0.001). MVPAOB was reduced by ~45.7 min (-33%) from Grade 6 to 9 (p<0.01). Significant main and interaction effects are noted for each fitness indicator (p<0.05). A backward stepwise multiple regression analysis determined significant shared variance in final APmath grade to the change scores from Grade 6 to Grade 9 in: Δ APmath , Δbackward obstacle course, Δsit and reach, and Δsit-ups (R2=0.494, F(4,180)=43.67, p<0.0001). A second regression was performed only for the youth who completed MVPAOB measurements. In this sub-sample, MVPAOB did not signficantly contribute to the model. Conclusion: Longitudinal changes in youth fitness and their delta change in APmath score accounted for 49.4% of the variance in the final math grade awarded at the end of Grade 9. Aerobic power, upper body strength, and muscular endurance share more common variance to final math grade in boys, whereas whole-body coordination was the more relevant index in girls; this finding suggests that future research exploring the relationship of AP and PF should not be limited to cardiorespiratory fitness, instead encompassing muscular and neuro-muscular components of PF.